Respuesta :
Answer: g(x)=12x^2+8
Step-by-step explanation:
original function f(x)=3x^2+2
Now to stretch function vertically and rename to g(x) we just multiply the function by 4;
g(x)=4(3x^2+2)=12x^2+8
Any questions feel free to ask. Thanks
The equation of the function f(x) after stretching is g(x) = 12x² + 8.
What is a function ?
A function is a law that relates a dependent and an independent variable.
The function given is
F(x) = 3x²+2
For when a function is vertically stretched
F'(x) = k .F(x)
k >1
here it is given that k = 4
The equation becomes
g(x) = 4( 3x²+2 )
g(x) = 12x² + 8
Therefore , The equation of the function f(x) after stretching is g(x) = 12x² + 8.
To know more about Function
https://brainly.com/question/12431044
#SPJ2